2017
DOI: 10.1007/s10453-017-9478-2
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between birch pollen, air pollution and weather types and their effect on antihistamine purchase in two Swedish cities

Abstract: Exposure to elevated air pollution levels can aggravate pollen allergy symptoms. The aim of this study was to investigate the relationships between airborne birch (Betula) pollen, urban air pollutants NO2, O3 and PM10 and their effects on antihistamine demand in Gothenburg and Malmö, Sweden, 2006–2012. Further, the influence of large-scale weather pattern on pollen-/pollution-related risk, using Lamb weather types (LWTs), was analysed. Daily LWTs were obtained by comparing the atmospheric pressure over a 16-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 45 publications
(62 reference statements)
1
17
0
Order By: Relevance
“…The lowest pollen concentration concerns cold, wet, and cloudy cyclonic types: SWCC, NWCC, and NWAC. Contrary to Grundström et al (2017) in terms of birch in Sweden, the pollen concentrations of Betula and Alnus in Wrocław are to a small extent influenced by wind speed. However, this is difficult to surmise, as the frequency of circulation types with calm wind conditions (especially from XX group of circulation types) favourable to pollen accumulation is very low (below the threshold frequency of 4% in pollen seasons).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The lowest pollen concentration concerns cold, wet, and cloudy cyclonic types: SWCC, NWCC, and NWAC. Contrary to Grundström et al (2017) in terms of birch in Sweden, the pollen concentrations of Betula and Alnus in Wrocław are to a small extent influenced by wind speed. However, this is difficult to surmise, as the frequency of circulation types with calm wind conditions (especially from XX group of circulation types) favourable to pollen accumulation is very low (below the threshold frequency of 4% in pollen seasons).…”
Section: Discussionmentioning
confidence: 64%
“…This complex description of weather conditions made it possible to analyse the influence of meteorology on pollen concentration and determine the circulation types with the highest and lowest pollen concentration. This approach was used earlier by Grundström et al (2017) for birch in Gothenburg and Malmö. Our results show that, similar to the Swedish study, the highest pollen concentrations for Betula and Alnus are noted for warm, sunny, and dry anticyclonic circulation types, especially when the anticyclone vorticity concerns the lower and upper troposphere.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the three SWPs persist for nearly a week, the CO concentrations increase by a maximum of 10–15% (Figures b, g, and h). Previous studies through observations and simulations suggested that the SWPs characterized by anticyclonic conditions are likely associated with high pollution episodes in the source regions (Grundström et al, ; Miao et al, ; Pope et al, , ; Shu et al, ). Studying CO transport in the free troposphere, Thomas and Devasthale () showed that this kind of SWPs lead to a 1% increase in free tropospheric CO over Nordic countries.…”
Section: Discussionmentioning
confidence: 99%
“…This increased bioavailability of airborne pollen allergens has been shown to cause an increased incidence of allergic disease. Several studies have shown that air pollution can affect pollen viability, production, and allergenicity . Hence, there is a need to identify conditions that coincide with high exposure to pollen and air pollution, and to determine the extent to which pollutants contribute to airway symptoms.…”
mentioning
confidence: 99%